ISRO misfired : the espionage case that shook India - Thomas, K. V. (Sage, 2019)
"An infamous espionage case took the country by storm in 1994 and destroyed the lives and careers of many people. It has finally been put to rest after 25 years. The main accused, Nambi Narayanan, was vindicated and in compliance with the Supreme Court's order, received 50 lakh compensation from the Kerala Government. He was also awarded the Padma Bhushan in 2019. But was all this too late? And what about the others who were accused? Has their honour been restored? Do we know the full story yet? Ex-IB officer K. V. Thomas reveals the long saga of interrogations, investigations and legal battles. Full of original disclosures, the book exposes deep secrets and closed-door conversations of India's most sensational spy case. 'The author, a senior official of the Indian Intelligence Bureau, who was associated in various capacities in the alleged ISRO espionage investigation speaks out the truth about what really happened in the so-called ISRO espionage case. The Supreme Court has now declared the case as false and concocted. The author talks about the victimological ill-effects and ramifications, exposing the reality from many hitherto unknown areas. The book will interest anyone concerned with criminal and victim justice.' Dr James Vadackumcherry, renowned criminologist and advocate, Neethi Law Chambers K. V. Thomas, Ex-IB officer, was closely associated with different phases of the 1994 ISRO espionage case"--